The Retroactive Re-Evaluation Technique with Pharaoh’s Daughter and the Nature of Solomon’s Corruption in 1 Kings 1-12 - Jeon, Yong Ho (Tyndale bulletin, 2011)
In the Solomon narrative in Kings (1 Kgs 1–12), Solomon’s faults are explicitly criticised only in 1 Kings 11, in relation to his marriage with foreign women. However, his intermarriage with Pharaoh’s daughter appears in earlier parts of the narrative (1 Kgs 3:1; 7:8; 9:16, 24) without any explicit criticism. Using a ‘reader-sensitive’ approach, which presumes that the author of the narrative tries to exploit the reader’s reading process and prior knowledge, we show that the writer is using a ‘retroactive re-evaluation technique’ in his reference to ‘Pharaoh’s daughter’ (the technique means that the author guides his reader to re-evaluate previous passages in light of new information). Additionally, through a theological reading of the narrative, the nature of Solomon’s corruption is revealed as his ‘return to Egypt’. This fits well with the ‘retroactive re-evaluation technique’, explaining why the references to ‘Pharaoh’s daughter’ are arranged in the way that they are.